1999
DOI: 10.1111/j.1745-9125.1999.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, Imprisonment, and Social Structures of Accumulation: Historical Contingency in the Rusche‐kirchheimer Hypothesis*

Abstract: This study explores the relationship between punishment and social structure by combining the work of Rusche and Kirchheimer with current theorizing regarding social structures of accumulation (SSAs). Specifically, we theorize that the unemployment-imprisonment (U-I) relationship is historically contingent. I n particular, we argue that qualitative changes in the configuration of labor markets, state strategies f o r managing surplus populations, and international relations across SSAs and stages within them r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Judges can view poor defendants as more culpable with less potential for rehabilitation (Kluegel 1990;Steffensmeier, Ulmer, and Kramer 1998, 770;Greenberg 1977;Albonetti 1991 rates were associated with high levels of incarceration (Michalowski and Carlson 1999). Indeed, recent studies by David Jacobs and his colleagues find no evidence for the effects of unemployment on incarceration in a time series or a panel study of 50 state in 1970, 1980(Jacobs and Helms 1996Jacobs and Carmichael 2001).…”
Section: The Labor Market and Social Controlmentioning
confidence: 99%
“…Judges can view poor defendants as more culpable with less potential for rehabilitation (Kluegel 1990;Steffensmeier, Ulmer, and Kramer 1998, 770;Greenberg 1977;Albonetti 1991 rates were associated with high levels of incarceration (Michalowski and Carlson 1999). Indeed, recent studies by David Jacobs and his colleagues find no evidence for the effects of unemployment on incarceration in a time series or a panel study of 50 state in 1970, 1980(Jacobs and Helms 1996Jacobs and Carmichael 2001).…”
Section: The Labor Market and Social Controlmentioning
confidence: 99%
“…In their meta-analyses of unemployment and imprisonment, for example, Chiricos and DeLone (1992) found that positive associations were more likely when imprisonment rates, rather than prison admission rates, were used as a dependent variable. Second, Michalowski and Carlson (1999) found that the relationships between economic conditions and punishment were dependent upon stages of economic development, at least within the United States. Third, factors that influence the use of imprisonment at the city or county level of analysis might not have a statistically significant association at larger levels of aggregation (Arvanites & Asher, 1998).…”
Section: Comparative Punishment Researchmentioning
confidence: 99%
“…Even though a meta-analysis of national imprisonment studies Downloaded by [Simon Fraser University] at 14:46 05 June 2016 found a significant positive association between unemployment and imprisonment (see Chiricos & DeLone, 1992), this relationship has not been supported in a series of recent national (Beckett & Western, 2001;Greenberg & West, 2001;Jacobs & Helms, 1996;Ruddell, 2004), and cross-national studies (Neapolitan, 2001;Ruddelt, 2005;Sutton, 2004). It is plausible that the failure to find a positive association depends on the economic era examined (see Michalowski & Carlson, 1999) and that other indicators of economic stress are more likely to influence the use of imprisonment. Because recent studies failed to find a positive association between imprisonment and unemployment, and because unemployment statistics were available for less than 100 nations, we did not include this variable.…”
Section: Independent Variablesmentioning
confidence: 99%
“…In their historical analysis of incarceration and unemployment, Michalowski and Carlson (1999) argue that labor market conditions affect punishment differently based on the social, political, and economic arrangements of the time. For instance, they demonstrate that unemployment and prison admission rates were positively correlated between 1948 and 1966 yet negatively correlated during the 1980s.…”
Section: Contextual Factors and Periodizationmentioning
confidence: 99%